2020
DOI: 10.1093/scan/nsaa082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HF-rTMS over the left and right DLPFC on proactive and reactive cognitive control

Abstract: Abstract Previous research supports the distinction between proactive and reactive control. Although the dorsolateral prefrontal cortex (DLPFC) has been consistently related to these processes, lateralization of proactive and reactive control is still under debate. We manipulated brain activity to investigate the role of the left and right DLPFC in proactive and reactive cognitive control. Using a single-blind, sham-controlled crossover within-subjects design, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…Among working memory, verbal memory is measured by typical retention tasks such as forward and backward digit span tests (58). Our results on digit span score improvements in the right DLPFC-treated group are consistent with previous findings that reported activation in the right DLPFC rather than in the left DLPFC in verbal episodic retrieval (59)(60)(61). In a more recent study, a neural mechanism involving the DLPFC in proactive and reactive control as a key regulator was suggested with a more specific role of the left DLPFC in proactive control and the implication of the right DLPFC in reactive control related to retrieval of verbal information (59).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among working memory, verbal memory is measured by typical retention tasks such as forward and backward digit span tests (58). Our results on digit span score improvements in the right DLPFC-treated group are consistent with previous findings that reported activation in the right DLPFC rather than in the left DLPFC in verbal episodic retrieval (59)(60)(61). In a more recent study, a neural mechanism involving the DLPFC in proactive and reactive control as a key regulator was suggested with a more specific role of the left DLPFC in proactive control and the implication of the right DLPFC in reactive control related to retrieval of verbal information (59).…”
Section: Discussionsupporting
confidence: 92%
“…Our results on digit span score improvements in the right DLPFC-treated group are consistent with previous findings that reported activation in the right DLPFC rather than in the left DLPFC in verbal episodic retrieval (59)(60)(61). In a more recent study, a neural mechanism involving the DLPFC in proactive and reactive control as a key regulator was suggested with a more specific role of the left DLPFC in proactive control and the implication of the right DLPFC in reactive control related to retrieval of verbal information (59). Our results of increments in MMSE subscores, registration and recall progression only by right DLPFC rTMS treatment are consistent with previous research about the right DLPFC, which is responsible for verbal retrieval and short-term memory such as reactive control.…”
Section: Discussionsupporting
confidence: 92%
“…Possibly, in the current study, tDCS could have promoted the employment of a general and sustained attentional strategy to a broader context of social evaluative threat, instead of trial-by-trial adjustments based on valence. Such reasoning would be consistent with research showing that neuro-stimulation of the DLPFC contributed to sustained cognitive resource allocation (Pulopulos et al, 2020), and the DLPFC and associated neural networks being implicated in the implementation of proactive regulatory mechanisms (Vanderhasselt et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…One possible interpretation, in light of the dual mode of control (DMC) framework (Braver, 2012), is that this area promotes the proactive mode of control and the active engagement with the task (detection of audiovisual incongruence) while the unisensory task-irrelevant auditory deviant forces a shift to a reactive mode. Indeed, in a recent rTMS study, the left DLPFC was found to be associated with the proactive mode of control (Pulopulos et al, 2020). The area is thought to hold representations of active goal information and is part of a network involved in the proactive mode, along with pre-SMA and parietal areas (Irlbacher et al, 2014).…”
Section: Dlpfc and Top-down Controlmentioning
confidence: 98%